Axitinib and/or bevacizumab with modified FOLFOX‐6 as first‐line therapy for metastatic colorectal cancer: A randomized phase 2 study. Issue 14 (19th April 2013) - Infante, Jeffrey R.; Reid, Tony R.; Cohn, Allen L.; Edenfield, William J.; Cescon, Terrence P.; Hamm, John T.; Malik, Imtiaz A.; Rado, Thomas A.; McGee, Philip J.; Richards, Donald A.; Tarazi, Jamal; Rosbrook, Brad; et al.
Abstract : BACKGROUND: In this multicenter, open‐label, randomized phase 2 trial, the authors evaluated the vascular endothelial growth factor receptor inhibitor axitinib, bevacizumab, or both in combination with chemotherapy as first‐line treatment of metastatic colorectal cancer (mCRC). METHODS: Patients with previously untreated mCRC were randomized 1:1:1 to receive continuous axitinib 5 mg twice daily, bevacizumab 5 mg/kg every 2 weeks, or axitinib 5 mg twice daily plus bevacizumab 2 mg/kg every 2 weeks, each in combination with modified 5‐fluorouracil/leucovorin/oxaliplatin (FOLFOX‐6). The primary endpoint was the objective response rate (ORR). RESULTS: In all, 126 patients were enrolled from August 2007 to September 2008. The ORR was numerically inferior in the axitinib arm (n = 42) versus the bevacizumab arm (n = 43; 28.6% vs 48.8%; 1‐sided P  = .97). Progression‐free survival (PFS) (11.0 months vs 15.9 months; 1‐sided P  = .57) and overall survival (OS) (18.1 months vs 21.6 months; 1‐sided P  = .69) also were numerically inferior in the axitinib arm. Similarly, efficacy endpoints for the axitinib/bevacizumab arm (n = 41) were numerically inferior (ORR, 39%; PFS, 12.5 months; OS, 19.7 months). The patients who received axitinib had fewer treatment cycles compared with other arms. Common all‐grade adverse events across all 3 treatment arms were fatigue, diarrhea, and nausea (all ≥49%). Hypertension and headache were more frequent in the patients who received axitinib. Patients in the bevacizumab arm had the longest treatment exposures and the highest rates of peripheral neuropathy. CONCLUSIONS: Neither the addition of continuous axitinib nor the axitinib/bevacizumab combination to FOLFOX‐6 improved ORR, PFS, or OS compared with bevacizumab as first‐line treatment of mCRC. Cancer 2013;119:2555–2563 . © 2013 American Cancer Society . Abstract : This randomized, phase 2 trial shows that objective response rates and progression‐free and overall survival are numerically inferior in patients who receive axitinib plus combined 5‐fluorouracil, leucovorin, and oxaliplatin (FOLFOX‐6) versus bevacizumab plus FOLFOX‐6. Shorter treatment duration and more discontinuations because of adverse events observed in the axitinib arm suggest that vascular endothelial growth factor receptor tyrosine kinase inhibitors plus chemotherapy may be somewhat less well tolerated than bevacizumab plus chemotherapy.